2020
DOI: 10.3168/jds.2020-18591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk bactofugation on the counts and diversity of thermoduric bacteria

Abstract: The objective of this work was to determine the effect of milk bactofugation on the counts and microbial diversity of mesophilic (MT), psychrotrophic (PT), and thermophilic (TT) thermoduric bacteria and its potential as a technological method to remove spoilage microorganisms resistant to pasteurization. Different batches of raw milk from 69 dairy farms divided into sets in 3 bulk tanks (A, B, C) were evaluated at different times during the technological process. As the raw milk was preheated (~55°C) immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…DNA was extracted from pure bacterial colonies using boiling lysis method [ 21 ]. The mechanism of penetration of CFDC through the OM is described in the literature as passing through the iron transport system [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from pure bacterial colonies using boiling lysis method [ 21 ]. The mechanism of penetration of CFDC through the OM is described in the literature as passing through the iron transport system [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although in low numbers, these sporeforming bacteria have been isolated from raw milk and milk products elsewhere and have been associated with spoilage [66,[95][96][97][98]. Lysinibacillus fusiformis is another spore-forming bacterium which has been isolated from raw milk in a previous study [99]. In the present study, two isolates of L. fusiformis were isolated from Farm 4 raw-milk samples, one from summer and one from winter.…”
Section: Discussionmentioning
confidence: 50%
“…B. licheniformis is one of the biggest concerns for the dairy industry throughout the world, especially for milk powder production ( Sadiq et al, 2016 ), as it is the predominant bacterial species found in raw milk and at all stages of dairy processing ( Banykó and Vyletělová, 2009 ; Gopal et al, 2015 ; Sadiq et al, 2016 , 2018 ). B. licheniformis and M. lacticum have been reported co-existing in whey protein concentrate ( Walsh et al, 2012 ) and raw milk ( Ribeiro-Júnior et al, 2020 ). These three species were shown to form synergistic biofilms in many combinations with other species like B. simplex , Kocuria salsicia , and opportunistic pathogens like Staphylococcus warneri .…”
Section: Discussionmentioning
confidence: 99%